Cement paste for well cementation in salt-containing stratum

By adjusting the formula of cement slurry, including adding dispersants, water-reducing agents, retarders, toughening agents, reinforcers and metasilicates, the problem of insufficient salt resistance and wide temperature adaptability in cementing wells with salt-containing formations has been solved, and the early development of cement slurry's strength and the improvement of compressive strength have been achieved.

CN119683909APending Publication Date: 2025-03-25CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202311242504.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-25
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The existing cement slurry used for cementing of salt-containing formations has insufficient salt resistance and wide temperate adaptability, resulting in the impact of cementing safety and quality.

Method used

The cement slurry consisting of G-grade cement, dispersant, water-reducing agent, retarder, toughening agent, reinforcer and metasilicate is used to improve the early strength, salt-resistant ability and temperature adaptability of the cement slurry by adjusting the proportion of formula and additives.

Benefits of technology

It has achieved the advantages of rapid development of early strength of cement slurry, strong resistance to salt invasion, wide temperature range and high compressive strength, and meets the requirements of cementing construction of thick salt paste layers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004467850990000091
    Figure BDA0004467850990000091
  • Figure BDA0004467850990000101
    Figure BDA0004467850990000101
  • Figure BDA0004467850990000102
    Figure BDA0004467850990000102
Patent Text Reader

Abstract

The invention relates to cement paste for well cementation in a salt-containing stratum, and belongs to the technical field of oil well cement. The cement paste for well cementation of the salt-containing stratum comprises sodium chloride, water and the following components in parts by mass: 100 parts of G-grade cement, 0.3-0.5 part of a dispersing agent, 1.4-1.8 parts of a fluid loss agent, 0.1-0.5 part of a retarder, 1-3 parts of a toughening agent, 1-3 parts of a reinforcing agent and 0.5-1 part of metasilicate. The cement paste for well cementation of the salt-containing stratum has the advantages of being fast in early strength development, high in salt invasion resistance, wide in adaptive temperature range, high in compressive strength and the like. In addition, the raw materials used in the cement paste for well cementation of the salt-containing stratum are wide in source and low in price. In addition, the cement paste for well cementation of the salt-containing stratum is rapid and stable in strength development, and can meet the requirements of well cementation construction of a thick salt-gypsum layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to cement slurry for well cementing in saline strata, belonging to the technical field of oil well cement. Background Art

[0002] Salt layers are soluble formations that are easily dissolved during drilling to form irregular wellbores and plastic flow. During the cementing process of salt layers, due to the imbalance between freshwater cement slurry and salt layers, salt will dissolve in the cement slurry, and alkali metals will migrate into the cement slurry, resulting in poor cement slurry performance and failure to form a good cement ring between the casing and the salt layer, affecting cementing safety and quality. In addition, during the hardening of cement slurry, the salt rock at the cement-salt rock interface will continue to dissolve and form micro-gaps, increasing the probability of gas or water channeling during cementing.

[0003] In order to solve the problems existing in conventional cement slurry when used for cementing in saline formations, salt water can be used instead of clean water to prepare cement slurry to reduce the influence of salt layer dissolution on cementing effect. For example, Chinese patent document CN106244124A discloses a salt-resistant high-density early-strength anti-channeling oil well cement slurry composed of six main components of oil well cement, iron ore powder, ultrafine cement, micro-silicon, manganese ore powder and styrene-butadiene latex anti-channeling agent, as well as several admixtures such as expansion agent, fluid loss reducer, retarder, dispersant and defoamer, which are mixed with 15.3wt% NaCl solution. The main performance of the cement slurry is stable, and it has the characteristics of good sedimentation stability, less free water, good flow performance, micro-expansion, early strength and good anti-channeling performance. Chinese patent document CN111303846A provides a brine high-density cement slurry composed of a basic formula and admixtures, wherein the basic formula includes G-grade oil well cement, high-temperature strength stabilizer, weighting agent, and anti-gas channeling agent; the admixtures include fluid loss reducer, retarder, drag reducer, 2% to 5% industrial salt, suspending agent, and defoamer. The cement slurry has good high-temperature sedimentation stability, and the prepared cement stone has high density, compressive strength, and displacement efficiency.

[0004] However, the performance of cement slurry currently prepared with brine will fluctuate when it comes into contact with salt-gypsum layer under formation conditions. In addition, the composition of cement slurry currently used for cementing in saline formations is complex, the formula performance adjustment is difficult, the performance is unstable, and the adaptability to wide temperate environments is poor. Summary of the invention

[0005] The purpose of the present invention is to provide a cement slurry for cementing in saline formations, which can solve the problems that the cement slurry currently used for cementing in saline formations has insufficient salt resistance and wide temperature zone adaptability.

[0006] In order to achieve the above objectives, the technical solution adopted by the cement slurry for cementing in saline formations of the present invention is:

[0007] A cement slurry for cementing in saline formations comprises sodium chloride, water and the following components in parts by weight: 100 parts of G-grade cement, 0.3-0.5 parts of dispersant, 1.4-1.8 parts of fluid loss reducer, 0.1-0.5 parts of retarder, 1-3 parts of toughening agent, 1-3 parts of reinforcing agent and 0.5-1 parts of metasilicate.

[0008] The cement slurry for cementing in saline formations of the present invention has the advantages of rapid early strength development, strong salt invasion resistance, wide temperature adaptability, high compressive strength, etc. In addition, the raw materials used in the cement slurry for cementing in saline formations of the present invention are widely available and inexpensive. In addition, the strength of the cement slurry for cementing in saline formations of the present invention develops rapidly and stably, and can meet the requirements of cementing construction in thick salt-gypsum layers.

[0009] Preferably, the reinforcing agent is microsilica and / or fumed silica. The reinforcing agent can enhance the compressive strength of cement paste, inhibit the strength decay of cement paste at high temperature, and improve the stability of cement slurry.

[0010] In order to improve the dispersion uniformity and stability of fumed silica in a water environment, preferably, the fumed silica is hydrophilic fumed silica. Hydrophilic fumed silica can be a commercially available product or prepared by itself, for example, according to the method in Chinese patent document CN106701283A, which specifically includes the following steps: after silicon tetrachloride is gasified at high temperature, gas phase hydrolysis is carried out at high temperature in the presence of hydrogen and oxygen, or air, to obtain fumed silica; then the fumed silica is purged with nitrogen-containing air to a pH between 4 and 6 to obtain the hydrophilic fumed silica. Or it includes the following steps: hydrolyzing volatile chlorosilane in a hydrogen-oxygen flame.

[0011] In order to improve the dispersibility of the reinforcing agent and improve the strength and stability of the cement slurry, preferably, the average particle size of the reinforcing agent is 0.1-0.3 μm. At the same time, in order to ensure that the microsilica powder and / or silicon dioxide can play a better reinforcing role, the mass fraction of silicon dioxide in the microsilica powder is not less than 90%, and the purity of the fumed silicon dioxide is not less than 99%.

[0012] Preferably, the toughening agent is biomass fiber, modified rubber powder; the modified rubber powder is rubber powder modified by silane coupling agent. Toughening agent can reduce the elastic modulus of cement paste and enhance the elastic toughness of cement paste. Preferably, the silane coupling agent is methacryloxysilane coupling agent and / or acryloxysilane coupling agent. For example, the silane coupling agent is γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropyltriethoxysilane, γ-methacryloxybutyltrimethoxysilane, acryloxypropyltrimethoxysilane. Modified rubber powder can be obtained commercially, for example, rubber powder modified by silane coupling agent produced by Hubei Jiahua Technology Co., Ltd.

[0013] In order to improve the dispersion uniformity and compatibility of the modified rubber powder and better exert the toughening effect, preferably, the particle size of the modified rubber powder is not less than 600 meshes.

[0014] In order to make the biomass fibers have a toughening effect and ensure that the prepared cement stone has a higher strength, preferably, the average length of the biomass fibers is 4 to 12 mm.

[0015] In order to reduce the cost, preferably, the biomass fiber is sugarcane fiber. In the present invention, the sugarcane fiber is obtained by crushing dried sugarcane bagasse.

[0016] Preferably, the dispersant is a sulfonated aldehyde-ketone condensate dispersant. Sulfonated aldehyde-ketone condensate can disperse cement particles well, form a stable cement slurry, and improve the suspension stability of the cement slurry. The sulfonated aldehyde-ketone condensate dispersant in the present invention is a commercially available product.

[0017] In order to make the dispersant disperse and mix evenly and exert the dispersing effect faster and better, preferably, in the sulfonated aldehyde-ketone condensate dispersant, the mass fraction of the sulfonated aldehyde-ketone condensate dispersant with a particle size greater than 0.315 mm is less than 12%.

[0018] Preferably, in the cementing cement composition, the mass fraction of sodium chloride is 6.75 to 9 parts.

[0019] Preferably, in the cementing cement composition, the mass fraction of water is 38.25 to 51 parts.

[0020] Preferably, the fluid loss reducer is a polymer obtained by polymerization of polymerized monomers; the polymerized monomers include 2-acrylamide-2-methylacrylic acid, N,N-dimethylacrylamide, acrylic acid and cationic polymerized monomers, and the cationic polymerized monomers are acryloyloxyethyl trimethylammonium chloride and / or acryloyloxyethyl trimethylammonium bromide; the number average molecular weight of the polymer is 50,000 to 100,000; the molar ratio of 2-acrylamide-2-methylacrylic acid repeating units, N,N-dimethylacrylamide repeating units, acrylic acid repeating units and cationic polymerized monomer repeating units in the polymer is (9 to 10): (0.5 to 1): (4 to 5): (0.5 to 1). The fluid loss reducer is a low molecular weight copolymer used to reduce the filtration loss of cement slurry to the formation, prevent the cement slurry performance from changing, and improve the stability of cement slurry performance. Through screening tests, it was found that when other types of fluid loss reducers, such as carboxymethyl cellulose, hydroxyethyl cellulose, or a polymer prepared by using any two or three polymerized monomers of 2-acrylamide-2-methylacrylic acid (AMPS), acrylamide (AM), and acrylic acid (AA) (the number average molecular weight of the prepared polymer is 50,000 to 100,000), were used for testing under the same conditions, the results showed that the fluid loss reduction effect of the cement slurry prepared by using the fluid loss reducer selected by the present invention was more than 10% stronger than that of the cement slurry prepared by using carboxymethyl cellulose, hydroxyethyl cellulose, or a polymer prepared by using any two or three polymerized monomers of 2-acrylamide-2-methylacrylic acid (AMPS), acrylamide (AM), and acrylic acid (AA) (the number average molecular weight of the prepared polymer is 50,000 to 100,000). At the same time, after the AMPS-AA copolymer fluid loss reducer was used to replace the fluid loss reducer in the cement slurry for cementing in saline formations of the present invention, the slurry became very viscous after stirring for 35 seconds and lost its pumpability.

[0021] Preferably, the retarder comprises a copolymer, an organic phosphonate and a polyaspartate; the copolymer is prepared by polymerization of 2-acrylamide-2-methylacrylic acid and itaconic acid, and the mass ratio of the 2-acrylamide-2-methylacrylic acid and itaconic acid is (8-9):(1-2); the mass ratio of the copolymer, the organic phosphonate and the polyaspartate is (18-22):(3-5):(0.5-1). For example, the mass ratio of the 2-acrylamide-2-methylacrylic acid and itaconic acid is 9:1; the mass ratio of the copolymer, the organic phosphonate and the polyaspartate is 20:3:0.5. The retarder is used to adjust the gel time of cementing slurry to ensure the safety of cementing operations.

[0022] Preferably, the method for preparing the copolymer comprises the following steps: 2-acrylamide-2-methylacrylic acid and itaconic acid are polymerized in a solvent under the action of an initiator; the initiator used to prepare the copolymer is a persulfate or an azo compound; the temperature of the polymerization reaction for preparing the copolymer is 50 to 60°C and the time is 4 to 6 hours. In order to ensure that the prepared copolymer can be used directly without impurity removal, preferably, the solvent used to prepare the copolymer is water. The main components of the system after the polymerization reaction are the copolymer and water. In order to reduce costs, the system after the polymerization reaction can be used directly, or the copolymer can be obtained after impurities are removed and then used in the form of a pure copolymer.

[0023] Preferably, the persulfate is an alkali metal persulfate or ammonium persulfate; the azo compound is azobis(isobutylene)imidazoline hydrochloride. Preferably, the mass ratio of 2-acrylamide-2-methylacrylic acid, itaconic acid and initiator used in the preparation of the copolymer is (16-18):(2-4):(0.2-0.5). The mass of water used in the preparation of the copolymer can be adjusted as needed, for example, the mass ratio of 2-acrylamide-2-methylacrylic acid, itaconic acid, water and initiator used in the preparation of the copolymer is (16-18):(2-4):100:(0.2-0.5).

[0024] In order to enhance the temperature and salt resistance of the retarder, preferably, the organic phosphonate is hydroxy ethylidene diphosphonate and / or alkyl diamine tetra methylene phosphate. For example, the hydroxy ethylidene diphosphonate is disodium hydroxy ethylidene diphosphonate and dipotassium hydroxy ethylidene diphosphonate; the alkyl diamine tetra methylene phosphate is ethylene diamine tetra methylene phosphate and hexamethylene diamine tetra methylene phosphate. For example, the alkyl diamine tetra methylene phosphate is sodium ethylene diamine tetra methylene phosphate and potassium ethylene diamine tetra methylene phosphate.

[0025] In order to enhance the temperature and salt resistance of the retarder, preferably, the polyaspartate is an alkali metal polyaspartate. For example, the polyaspartate is sodium polyaspartate or potassium polyaspartate. Preferably, the number average molecular weight of the polyaspartate is 2500 to 5000.

[0026] In order to accelerate the early strength development of cementing slurry, preferably, the metasilicate is an alkali metal metasilicate or a hydrate of an alkali metal metasilicate. For example, the metasilicate is sodium metasilicate.

[0027] Preferably, the cement slurry for cementing in saline formations is prepared by a method comprising the following steps: uniformly mixing formulated amounts of cement, dispersant, fluid loss reducer, toughening agent, reinforcing agent and metasilicate to obtain a dry mix; uniformly mixing formulated amounts of coagulant, water and sodium chloride to obtain a wet mix; then adding the dry mix to the wet mix at a stirring speed of 3800 to 4200 r / min, and after the dry mix is ​​added, increasing the stirring speed to 11500 to 12500 r / min, and continuing stirring for not less than 35 seconds to obtain cement slurry for cementing in saline formations. DETAILED DESCRIPTION

[0028] The technical solution of the present invention is further described below in conjunction with specific embodiments.

[0029] Example 1

[0030] The cement slurry for cementing in saline formations of this embodiment is composed of the following components by weight: 100 parts of cement, 0.5 parts of dispersant, 1.4 parts of fluid loss reducer, 0.1 parts of retarder, 1 part of toughening agent, 1 part of reinforcing agent, 0.5 parts of metasilicate, 6.75 parts of sodium chloride, and 38.25 parts of water;

[0031] The cement is G-grade oil well cement, the dispersant is a sulfonated aldehyde-ketone condensate dispersant (in the sulfonated aldehyde-ketone condensate dispersant, the mass fraction of the sulfonated aldehyde-ketone condensate dispersant with a particle size greater than 0.315 mm is less than 12%), the metasilicate is sodium metasilicate, the reinforcing agent is microsilica powder (the average particle size of the microsilica powder is 0.1 μm, and the mass fraction of silicon dioxide in the microsilica powder is not less than 90%), and the toughening agent is biomass fiber (the biomass fiber is sugarcane fiber, which is obtained by crushing dried sugarcane bagasse, and the average length of the sugarcane fiber is 8 mm);

[0032] The fluid loss reducer of this embodiment is prepared by polymerization of 2-acrylamide-2-methacrylic acid, N,N-dimethylacrylamide, acrylic acid and acryloyloxyethyltrimethylammonium chloride. The number average molecular weight of the fluid loss reducer is 50,000 to 100,000. The molar ratio of the 2-acrylamide-2-methacrylic acid repeating unit, the N,N-dimethylacrylamide repeating unit, the acrylic acid repeating unit and the acryloyloxyethyltrimethylammonium chloride repeating unit in the fluid loss reducer is 10:0.5:5:0.5.

[0033] The retarder of the present embodiment is composed of water, copolymer, organic phosphonate and polyaspartate, the mass ratio of water, copolymer, organic phosphonate and polyaspartate is 100:20:3:0.5, the organic phosphonate is hydroxyethylidene diphosphonate, the hydroxyethylidene diphosphonate is disodium hydroxyethylidene diphosphonate, the polyaspartate is sodium polyaspartate, and the number average molecular weight of sodium polyaspartate is 2500-5000; the retarder of the present embodiment is prepared by a method comprising the following steps: first, 2-acrylamido-2-methylacrylic acid and itaconic acid are added to water; The polymerization monomer solution is adjusted to neutrality with a 30% sodium hydroxide solution to obtain a mixed solution, and the mixed solution is heated to 50° C., sodium persulfate is added to the mixed solution under stirring, and the mixture is stirred at a constant temperature for 4 hours to obtain a dispersion of a copolymer, wherein the mass ratio of 2-acrylamide-2-methylacrylic acid, itaconic acid, water and sodium persulfate used in preparing the dispersion of the copolymer is 18:2:100:0.2; and the dispersion of the copolymer, the organic phosphonate and the polyaspartate are stirred evenly to obtain.

[0034] Example 2

[0035] The cement slurry for cementing in saline formations of this embodiment is composed of the following components by weight: 100 parts of cement, 0.5 parts of dispersant, 1.5 parts of fluid loss reducer, 0.5 parts of retarder, 2 parts of toughening agent, 3 parts of reinforcing agent, 0.5 parts of metasilicate, 7.05 parts of sodium chloride, and 39.95 parts of water;

[0036] The cement is G-grade oil well cement, the dispersant is a sulfonated aldehyde-ketone condensate dispersant (among the sulfonated aldehyde-ketone condensate dispersants, the mass fraction of the sulfonated aldehyde-ketone condensate dispersants with a particle size greater than 0.315 mm is less than 12%), the metasilicate is potassium metasilicate, the reinforcing agent is hydrophilic fumed silica (the average particle size of the hydrophilic fumed silica is 0.3 μm, and the purity is not less than 99%), and the toughening agent is modified rubber powder (the particle size of the modified rubber powder is 600 meshes, and the modified rubber powder is rubber powder modified with γ-methacryloxypropyltrimethoxysilane);

[0037] The fluid loss reducer of this embodiment is prepared by polymerization of 2-acrylamide-2-methylacrylic acid, N,N-dimethylacrylamide, acrylic acid and acryloyloxyethyltrimethylammonium bromide. The number average molecular weight of the fluid loss reducer is 50,000 to 100,000. The molar ratio of the 2-acrylamide-2-methylacrylic acid repeating unit, the N,N-dimethylacrylamide repeating unit, the acrylic acid repeating unit and the acryloyloxyethyltrimethylammonium bromide repeating unit in the fluid loss reducer is 9:1:4:1.

[0038] The retarder of the present embodiment is composed of water, copolymer, organic phosphonate and polyaspartate, the mass ratio of water, copolymer, organic phosphonate and polyaspartate is 100:20:5:1, the organic phosphonate is hydroxyethylidene diphosphonate, the hydroxyethylidene diphosphonate is dipotassium hydroxyethylidene diphosphonate, the polyaspartate is potassium polyaspartate, and the number average molecular weight of potassium polyaspartate is 2500-5000; the retarder of the present embodiment is prepared by a method comprising the following steps: first, 2-acrylamido-2-methylacrylic acid and itaconic acid are added into water; , stirring evenly to obtain a polymerization monomer solution, then adjusting the polymerization monomer solution to neutrality with a 30% sodium hydroxide solution to obtain a mixed solution, then heating the mixed solution to 60° C., adding sodium persulfate to the mixed solution while stirring, and reacting at a constant temperature and stirring for 6 hours to obtain a copolymer dispersion, wherein the mass ratio of 2-acrylamide-2-methylacrylic acid, itaconic acid, water and sodium persulfate used in preparing the copolymer dispersion is 16:4:100:0.5; then stirring the copolymer dispersion, organic phosphonate and polyaspartate evenly to obtain.

[0039] Example 3

[0040] The cement slurry for cementing in saline formations of this embodiment is composed of the following components by weight: 100 parts of cement, 0.5 parts of dispersant, 1.5 parts of fluid loss reducer, 0.3 parts of retarder, 2 parts of toughening agent, 3 parts of reinforcing agent, 1 part of metasilicate, 7.5 parts of sodium chloride, and 42.5 parts of water;

[0041] The cement is G-grade oil well cement, the dispersant is a sulfonated aldehyde-ketone condensate dispersant (in the sulfonated aldehyde-ketone condensate dispersant, the mass fraction of the sulfonated aldehyde-ketone condensate dispersant with a particle size greater than 0.315 mm is less than 12%), the metasilicate is sodium metasilicate, the reinforcing agent is microsilica powder (the average particle size of the microsilica powder is 0.1 μm, and the mass fraction of silicon dioxide in the microsilica powder is not less than 90%), and the toughening agent is modified rubber powder (the particle size of the modified rubber powder is 600 meshes, and the modified rubber powder is rubber powder modified with γ-methacryloxypropyltrimethoxysilane);

[0042] The fluid loss reducer of this embodiment is prepared by polymerization of 2-acrylamide-2-methacrylic acid, N,N-dimethylacrylamide, acrylic acid and acryloyloxyethyl trimethylammonium chloride. The number average molecular weight of the fluid loss reducer is 50,000 to 100,000. The molar ratio of the 2-acrylamide-2-methacrylic acid repeating unit, the N,N-dimethylacrylamide repeating unit, the acrylic acid repeating unit and the acryloyloxyethyl trimethylammonium chloride repeating unit in the fluid loss reducer is 9:0.5:4.5:1.

[0043] The retarder of the present embodiment is composed of water, copolymer, organic phosphonate and polyaspartate, the mass ratio of water, copolymer, organic phosphonate and polyaspartate is 100:20:4:0.8, the organic phosphonate is alkyl diamine tetramethylene phosphate, the alkyl diamine tetramethylene phosphate is sodium ethylene diamine tetramethylene phosphate, the polyaspartate is sodium polyaspartate, and the number average molecular weight of sodium polyaspartate is 2500-5000; the retarder of the present embodiment is prepared by a method comprising the following steps: first, 2-acrylamide-2-methylacrylic acid and itaconic acid are added The mixture is added into water and stirred evenly to obtain a polymerization monomer solution, and then the polymerization monomer solution is adjusted to neutrality with a 30% sodium hydroxide solution to obtain a mixed solution, and then the mixed solution is heated to 55° C., sodium persulfate is added to the mixed solution while stirring, and the mixture is stirred at a constant temperature for 5 hours to obtain a dispersion of a copolymer, wherein the mass ratio of 2-acrylamide-2-methylacrylic acid, itaconic acid, water and sodium persulfate used in preparing the dispersion of the copolymer is 17:3:100:0.3; and then the dispersion of the copolymer, the organic phosphonate and the polyaspartate are stirred evenly to obtain the dispersion.

[0044] Example 4

[0045] The cement slurry for cementing in saline formations of this embodiment is composed of the following components by weight: 100 parts of cement, 0.3 parts of dispersant, 1.8 parts of fluid loss reducer, 0.5 parts of retarder, 3 parts of toughening agent, 3 parts of reinforcing agent, 1 part of metasilicate, 9 parts of sodium chloride, and 51 parts of water;

[0046] The cement is G-grade oil well cement, the dispersant is a sulfonated aldehyde-ketone condensate dispersant (in the sulfonated aldehyde-ketone condensate dispersant, the mass fraction of the sulfonated aldehyde-ketone condensate dispersant with a particle size greater than 0.315 mm is less than 12%), the metasilicate is sodium metasilicate, the reinforcing agent is microsilica powder (the average particle size of the microsilica powder is 0.3 μm, and the mass fraction of silicon dioxide in the microsilica powder is not less than 90%), and the toughening agent is composed of biomass fiber (the biomass fiber is sugarcane fiber, which is obtained by crushing dried sugarcane bagasse, and the average length of the sugarcane fiber is 4 mm) and modified rubber powder (the particle size of the modified rubber powder is 600 mesh, and the modified rubber powder is rubber powder modified by γ-methacryloxypropyltrimethoxysilane) in a mass ratio of 1:2;

[0047] The fluid loss reducer of this embodiment is prepared by polymerization of 2-acrylamide-2-methylacrylic acid, N,N-dimethylacrylamide, acrylic acid and acryloyloxyethyltrimethylammonium chloride. The number average molecular weight of the fluid loss reducer is 50,000 to 100,000. The molar ratio of the 2-acrylamide-2-methylacrylic acid repeating unit, the N,N-dimethylacrylamide repeating unit, the acrylic acid repeating unit and the acryloyloxyethyltrimethylammonium chloride repeating unit in the fluid loss reducer is 10:0.5:4:0.5.

[0048] The retarder of the present embodiment is composed of water, copolymer, organic phosphonate and polyaspartate, the mass ratio of water, copolymer, organic phosphonate and polyaspartate is 100:22:3:0.5, the organic phosphonate is hydroxyethylidene diphosphonate, the hydroxyethylidene diphosphonate is disodium hydroxyethylidene diphosphonate, the polyaspartate is sodium polyaspartate, and the number average molecular weight of sodium polyaspartate is 2500-5000; the retarder of the present embodiment is prepared by a method comprising the following steps: first, 2-acrylamido-2-methylacrylic acid and itaconic acid are added to water; The polymerization monomer solution is adjusted to neutrality with a 30% sodium hydroxide solution to obtain a mixed solution, and the mixed solution is heated to 50° C., sodium persulfate is added to the mixed solution under stirring, and the mixture is stirred at a constant temperature for 6 hours to obtain a dispersion of a copolymer, wherein the mass ratio of 2-acrylamide-2-methylacrylic acid, itaconic acid, water and sodium persulfate used in preparing the dispersion of the copolymer is 18:4:100:0.2; and the dispersion of the copolymer, the organic phosphonate and the polyaspartate are stirred evenly to obtain the dispersion of the copolymer.

[0049] Example 5

[0050] The cement slurry for cementing in saline formations of this embodiment is composed of the following components by weight: 100 parts of cement, 0.5 parts of dispersant, 1.5 parts of fluid loss reducer, 0.5 parts of retarder, 1 part of toughening agent, 1 part of reinforcing agent, 0.5 parts of metasilicate, 6.75 parts of sodium chloride, and 38.25 parts of water;

[0051] The cement is G-grade oil well cement, the dispersant is a sulfonated aldehyde-ketone condensate dispersant (in the sulfonated aldehyde-ketone condensate dispersant, the mass fraction of the sulfonated aldehyde-ketone condensate dispersant with a particle size greater than 0.315 mm is less than 12%), the metasilicate is sodium metasilicate, the reinforcing agent is microsilica powder (the average particle size of the microsilica powder is 0.2 μm, and the mass fraction of silicon dioxide in the microsilica powder is not less than 90%), and the toughening agent is biomass fiber (the biomass fiber is sugarcane fiber, which is obtained by crushing dried sugarcane bagasse, and the average length of the sugarcane fiber is 12 mm);

[0052] The fluid loss reducer of this embodiment is prepared by polymerization of 2-acrylamide-2-methylacrylic acid, N,N-dimethylacrylamide, acrylic acid and acryloyloxyethyltrimethylammonium chloride. The number average molecular weight of the fluid loss reducer is 50,000 to 100,000. The molar ratio of the 2-acrylamide-2-methylacrylic acid repeating unit, the N,N-dimethylacrylamide repeating unit, the acrylic acid repeating unit and the acryloyloxyethyltrimethylammonium chloride repeating unit in the fluid loss reducer is 9:1:4:1.

[0053] The retarder of the present embodiment is composed of water, copolymer, organic phosphonate and polyaspartate, the mass ratio of water, copolymer, organic phosphonate and polyaspartate is 100:18:3:0.5, the organic phosphonate is hydroxyethylidene diphosphonate, the hydroxyethylidene diphosphonate is disodium hydroxyethylidene diphosphonate, the polyaspartate is sodium polyaspartate, and the number average molecular weight of sodium polyaspartate is 2500-5000; the retarder of the present embodiment is prepared by a method comprising the following steps: first, 2-acrylamido-2-methylacrylic acid and itaconic acid are added to water; The polymerization monomer solution is adjusted to neutrality with a 30% sodium hydroxide solution to obtain a mixed solution, and the mixed solution is heated to 60° C., sodium persulfate is added to the mixed solution while stirring, and the mixture is stirred at a constant temperature for 4 hours to obtain a dispersion of the copolymer. The mass ratio of 2-acrylamide-2-methylacrylic acid, itaconic acid, water and sodium persulfate used in preparing the dispersion of the copolymer is 16:2:100:0.2; the dispersion of the copolymer, the organic phosphonate and the polyaspartate are then stirred to obtain.

[0054] The preparation method of cement slurry for cementing saline formations of Examples 1-5 is as follows: stir the formulated amounts of cement, dispersant, fluid loss reducer, toughening agent, reinforcing agent and metasilicate evenly to obtain a dry mix; stir the formulated amounts of coagulant, water and sodium chloride (water and sodium chloride are used in the form of brine) evenly to obtain a wet mix; then add the dry mix to the wet mix at a stirring speed of 3800 to 4200 r / min. After the dry mix is ​​added, increase the stirring speed to 11500 to 12500 r / min, and continue stirring for 35 seconds to obtain cement slurry for cementing saline formations.

[0055] Comparative Example 1

[0056] The difference between the cement slurry for saline formation cementing in this comparative example and the cement slurry for saline formation cementing in Example 1 is that the mass fraction of metasilicate in the cement slurry for saline formation cementing in this comparative example is 0 parts, and the mass fraction of retarder is 0.6 parts.

[0057] Comparative Example 2

[0058] The difference between the cement slurry for saline formation cementing in this comparative example and the cement slurry for saline formation cementing in Example 1 is that the mass fraction of metasilicate in the cement slurry for saline formation cementing in this comparative example is 0.6 parts, and the mass fraction of retarder is 0 parts.

[0059] Experimental Example 1

[0060] In order to evaluate the performance of the cement slurry for cementing in saline formations of Examples 1-5 and Comparative Examples 1-2, the water loss, density, sedimentation stability, rheology, thickening test and compressive strength of each cement slurry for cementing in saline formations were tested according to the requirements of the standard GB / T19139-2012 "Test Methods for Oil Well Cement" and the standard SY / T 6544-2017 "Performance Requirements for Oil Well Cement Slurry". Among them, the water loss test conditions are temperature 100°C and pressure 6.9MPa. The sedimentation stability test method is as follows: the cement slurry is cured in a pressurized thickener for 20 minutes, then poured into a 500mL beaker and left to stand for 2 hours, and finally the density difference between the upper and lower layers of the cement slurry is obtained by testing. The rheology is evaluated by testing the viscosity at different speeds (the speeds are 100r / min and 300r / min, respectively). The thickening experiment is tested at 100°C and 61MPa. The compressive strength is obtained by testing the cement slurry after curing it at 100°C and 21 MPa for 24 hours. The test results of water loss, sedimentation stability, rheology, thickening test and compressive strength of the cement slurry for cementing in saline formations of Examples 1-5 and Comparative Examples 1-2 are shown in Table 1.

[0061] Table 1 Test results of water loss, stability, rheology, thickening time and compressive strength of cement slurry for cementing in various saline formations

[0062]

[0063] As shown in Table 1, the density of the cement slurry for cementing in saline formations of the present invention can be between 1.80 and 2.0 g / cm 3 The density difference between the upper and lower density should not exceed 0.01g / cm 3 . At the same time, the water loss of cementing slurry can be controlled within 44mL, and the system as a whole has good stability. The cementing cement slurry system maintains good right-angle thickening performance, and the thickening transition time is much less than the requirements of the national standard technical indicators (≤40min). Comparing Example 1 with Comparative Examples 1-2, metasilicate and retarder have a synergistic effect to prolong the thickening time of cementing cement slurry and shorten the thickening transition time. At the same time, the addition of metasilicate will reduce the water loss of cement slurry, shorten the thickening transition time, and increase the 24h compressive strength of cement stone.

[0064] Experimental Example 2

[0065] In order to evaluate the salt resistance of the cement slurry for cementing in saline formations of Examples 1-5 and Comparative Example 1, sodium chloride was added to the cement slurry for cementing in saline formations of each Example and Comparative Example 1 until the mass fraction of sodium chloride in the cement slurry was 35% to obtain a test solution, and then the prepared test solution was tested for water loss, rheology, thickening time and compressive strength according to the method in Experimental Example 1. The test results are shown in Table 2.

[0066] Table 2 Test results of salt resistance of cement slurry for cementing in saline formations

[0067]

[0068] As shown in Table 2, the cement slurry for cementing in saline formations provided by the present invention still maintains good flowability when the salt capacity in the system is nearly saturated, with a water loss of <50 mL at 100°C, and a compressive strength of the cement paste of more than 17 MPa after curing for 24 hours, meeting the national standard requirements for cementing. Compared with the test results of Comparative Example 1, it is found that the presence of metasilicate can promote the formation of calcium silicate gel during cement hydration, reduce the water loss of cement slurry, and accelerate the strength development of cement paste.

[0069] Experimental Example 3

[0070] In order to evaluate the temperature adaptability of the cement slurry for cementing in saline formations of Examples 1-5 and Comparative Example 1, a wide temperature zone adaptability test of the cement slurry was carried out in accordance with the provisions of the standard GB / T 19139-2012 "Test Methods for Oil Well Cement". Specifically, the water loss of the cement slurry for cementing in saline formations was tested at different temperatures and 6.9 MPa, and the compressive strength was tested at different temperatures and pressures. The test results are shown in Table 3.

[0071] Table 3 Test results of the temperature adaptability of cement slurry for cementing in saline formations

[0072]

[0073]

[0074] As shown in Table 3, the cement slurry for cementing in saline formations of the present invention can control the water loss below 50 mL in the range of 40-110°C, and after curing for 48 hours, the strength of the cement paste reaches above 21 MPa, which is suitable for cementing in a wide temperate zone with a long sealing section. According to Example 1 and Comparative Example 1, it can be seen that the addition of metasilicate significantly accelerates the development of cement paste strength.

[0075] Experimental Example 4

[0076] In order to evaluate the long-term sealing stability of the cement slurries for cementing in saline formations of Examples 1-5 and Comparative Example 1, a compressive strength test was performed in accordance with the provisions of the standard GB / T 19139-2012 "Test methods for oil well cement". Specifically, the cement composition was cured at 100°C and 21MPa, and then the compressive strength of the cement paste was tested at different curing times. The test results are shown in Table 4.

[0077] Table 4 Test results of long-term sealing stability of cement slurry for cementing in saline formations

[0078]

[0079] As shown in Table 4, the compressive strength of the cement slurry for cementing in saline formations of the present invention can reach more than 20 MPa after curing for 24 hours at 100°C and 21 MPa, and the compressive strength exceeds 40 MPa after curing for 28 days, showing good stability. By comparing Example 1 with Comparative Example 1, it is found that metasilicate mainly affects the early strength development of cement paste, and has little effect on the final strength of cement paste.

[0080] In summary, the cement slurry for cementing in saline formations provided by the present invention has good salt resistance, is suitable for cementing in a wide temperate zone with a bottom hole circulation temperature of 40 to 110°C, has right-angle thickening and a short transition time, and can ensure long-term stable sealing. The cement slurry for cementing in saline formations provided by the present invention has excellent salt resistance, a wide temperature adaptability range, and rapid and stable strength development, which can meet the requirements of cementing construction in thick salt-gypsum layers.

Claims

1. A cement slurry for cementing in saline formations, characterized in that: It includes sodium chloride, water and the following components in parts by weight: 100 parts of grade G cement, 0.3-0.5 parts of dispersant, 1.4-1.8 parts of fluid loss reducer, 0.1-0.5 parts of retarder, 1-3 parts of toughening agent, 1-3 parts of reinforcing agent and 0.5-1 parts of metasilicate.

2. The cement slurry for cementing in saline formations according to claim 1, characterized in that: The reinforcing agent is microsilica powder and / or fumed silica.

3. The cement slurry for cementing in saline formations according to claim 2, characterized in that: The average particle size of the reinforcing agent is 0.1 to 0.3 μm.

4. The cement slurry for cementing in saline formations according to claim 1, characterized in that: The toughening agent is biomass fiber and / or modified rubber powder; the modified rubber powder is rubber powder modified by a silane coupling agent.

5. The cement slurry for cementing in saline formations according to claim 4, characterized in that: The average length of the biomass fiber is 4-12 mm; the particle size of the modified rubber powder is not less than 600 meshes; and the silane coupling agent is a methacryloxy silane coupling agent and / or an acryloxy silane coupling agent.

6. The cement slurry for cementing in saline formations according to claim 4 or 5, characterized in that: The silane coupling agent is γ-methacryloxypropyl trimethoxysilane, γ-methacryloxypropyl triethoxysilane, γ-methacryloxybutyl trimethoxysilane, and acryloxypropyl trimethoxysilane.

7. The cement slurry for cementing in saline formations according to any one of claims 1 to 5, characterized in that: The dispersant is a sulfonated aldehyde-ketone condensate dispersant; the metasilicate is an alkali metal metasilicate or a hydrate of an alkali metal metasilicate; the mass fraction of the sodium chloride is 6.75 to 9 parts; and the mass fraction of the water is 38.25 to 51 parts.

8. The cement slurry for cementing in saline formations according to any one of claims 1 to 5, characterized in that: The fluid loss additive is a polymer obtained by polymerization reaction of polymerization monomers; the polymerization monomers include 2-acrylamide-2-methylacrylic acid, N,N-dimethylacrylamide, acrylic acid and cationic polymerization monomers, and the cationic polymerization monomers are acryloyloxyethyltrimethylammonium chloride and / or acryloyloxyethyltrimethylammonium bromide; the number average molecular weight of the polymer is 50,000 to 100,000; the molar ratio of 2-acrylamide-2-methylacrylic acid repeating units, N,N-dimethylacrylamide repeating units, acrylic acid repeating units and cationic polymerization monomer repeating units in the polymer is (9 to 10):(0.5 to 1):(4 to 5):(0.5 to 1).

9. The cement slurry for cementing in saline formations according to any one of claims 1 to 5, characterized in that: The retarder comprises a copolymer, an organic phosphonate and a polyaspartate; the copolymer is prepared by polymerization of 2-acrylamide-2-methylacrylic acid and itaconic acid, and the mass ratio of the 2-acrylamide-2-methylacrylic acid and itaconic acid is (8-9):(1-2); the mass ratio of the copolymer, the organic phosphonate and the polyaspartate is (18-22):(3-5):(0.5-1).

10. The cement slurry for cementing in saline formations according to claim 9, characterized in that: The preparation method of the copolymer comprises the following steps: 2-acrylamide-2-methylacrylic acid and itaconic acid are subjected to polymerization reaction in a solvent under the action of an initiator; the initiator used for preparing the copolymer is a persulfate or an azo compound; the polymerization reaction temperature for preparing the copolymer is 50-60° C. and the time is 4-6 hours; the mass ratio of 2-acrylamide-2-methylacrylic acid, itaconic acid and initiator used in preparing the copolymer is (16-18):(2-4):(0.2-0.5).

Citation Information

Patent Citations

  • Anti-salt high-density early-strength anti-channeling oil well cement slurry

    CN106244124A

  • Lubricating oil composition and preparation method thereof

    CN106701283A

  • Oil-gas well cementing saline water high-density cement paste

    CN111303846A

  • Oil well cement fluid loss agent for solving problem of thickening and core wrapping of cement paste and preparation method thereof

    CN111153624A

  • Cement paste system and preparation method thereof

    CN112299757A

Cited By

  • Oil well cement retarder

    CN119684982A